Photosensitive resin laminate and application thereof
By using a photosensitive resin laminated body composed of a multi-layer photosensitive resin layer, the problem of poor bonding of the existing photoresist film is solved, and the effect of good bonding, storage and operability of the high-thick photoresist film is achieved.
Patent Information
- Application Number
- CN202410010516.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-01
- Filing Date
- 2024-01-04
- Publication Date
- 2025-03-04
AI Technical Summary
In the printed circuit board industry, the existing photoresist films have poor fit and are prone to bubbles or wrinkles, resulting in defects in subsequent electroplating or etching processing.
The photosensitive resin laminated body composed of a multi-layer photosensitive resin layer is used to improve the bondability, storage and operability of the photoresist film by controlling the properties of the gas phase chromatography.
It achieves the effect of good bonding, storage and operability of the high-thickness photosensitive resin laminated body, and is suitable for bulk circuit packaging of 2.5D and 3D.
Smart Images

Figure CN119556523A_ABST
Abstract
Description
Technical Field The present invention relates to a photosensitive resin laminate, and more particularly to a photosensitive resin laminate having a high total thickness, and applications of the photosensitive resin laminate. Background Art Photosensitive resin film is a resin film that undergoes chemical changes after being exposed to light. It can be used as a photoresist film in various electronic fields. Photoresist films are divided into positive photoresist films and negative photoresist films according to the changes after exposure and development. After exposure, the part of the positive photoresist film exposed to light will dissolve during development, leaving the pattern of the unexposed part after development. After exposure, the part of the negative photoresist film not exposed to light will dissolve during development, leaving the pattern of the exposed part after development. In the printed circuit board (PCB) industry, photoresist films must be used for etching or electroplating procedures to form circuit patterns. As electronic components become more complex and larger, the printed circuit board industry has an increasing demand for thick photoresist films with high aspect ratios. However, existing photoresist films have poor adhesion, or have bubbles or wrinkles, which lead to defects in subsequent electroplating or etching processes. Summary of the invention In view of the above technical problems, the present invention aims to provide a solution to improve the adhesion, storage and operability of the photoresist film. After research, it is found that the above technical problems can be solved by a photosensitive resin laminate composed of multiple photosensitive resin layers. Therefore, an object of the present invention is to provide a photosensitive resin laminate, which is composed of two or more photosensitive resin layers and contains a second component, wherein: When the photosensitive resin laminate is characterized by gas chromatography with toluene added as an internal standard substance, the second component has an elution peak at 0.55 minutes to 1.30 minutes, and a toluene elution peak at 1.32 minutes to 1.65 minutes, and the following relationship is satisfied: The units of the amount of toluene added and the mass of the photosensitive resin laminate are grams (g); and The total thickness of the photosensitive resin laminate is 100 micrometers to 600 micrometers. In some embodiments of the present invention, the gas chromatography analysis is performed by dissolving the photosensitive resin laminate in propylene glycol monomethyl ether and adding toluene as an internal standard substance to form a solution, and the analysis is performed under the following conditions: the column is a stainless steel column with a length of 3 meters, an outer diameter of 1 / 8 inches, and a wall thickness of 0.02 inches; the filler is a porous polymer stationary phase filler; the carrier gas is nitrogen with a flow rate of 20 milliliters per minute (mL / min), and the pressure at the helium source end is 5 kilograms of force per square centimeter (kgf / cm2 ); the temperature rising condition is a step-by-step method, which is to maintain at 80°C for 0.1 minute, then increase from 80°C to 96°C at a heating rate of 4°C / min, then increase from 96°C to 135°C at a heating rate of 10°C / min, and maintain at 135°C for 2 minutes; the injection port temperature is 180°C; the solution injection volume is 3 microliters (μL); and the detector is a thermal conductivity detector at 200°C. In some embodiments of the present invention, each of the photosensitive resin layers independently has a thickness of 50 micrometers to 300 micrometers. In some embodiments of the present invention, the photosensitive resin laminate is composed of two to four photosensitive resin layers. In some embodiments of the present invention, each of the photosensitive resin layers is independently a dry film. In some embodiments of the present invention, the photosensitive resin layers each independently comprise: (A) an alkali-soluble polymer; (B) a component containing an ethylenically unsaturated compound; and (C) a photopolymerization initiator. In some embodiments of the present invention, the ethylenically unsaturated compound-containing component (B) comprises a bifunctional acrylate compound. In some embodiments of the present invention, the content of the bifunctional acrylate compound is 60% by weight or more based on the weight of the component (B) containing the ethylenically unsaturated compound. Another object of the present invention is to provide a composite laminate comprising the photosensitive resin laminate as described above, and a non-photosensitive resin film located on at least one surface of the photosensitive resin laminate. In some embodiments of the present invention, the non-photosensitive resin film is selected from the following group: polyethylene terephthalate film, polyolefin film and a composite thereof. In order to make the above-mentioned objectives, technical features and advantages of the present invention more obvious and easy to understand, some specific implementation schemes are described in detail below. DETAILED DESCRIPTION Some specific embodiments according to the present invention will be described in detail below; however, the present invention can also be practiced in a variety of different forms, and the protection scope of the present invention should not be interpreted as being limited to what is stated in the description. Unless otherwise specified, the terms "a", "an", "the" and similar terms used in the specification and claims should be understood to include both the singular and the plural. Unless otherwise specified, the terms “first”, “second” and the like used in the specification and the claims are merely used to distinguish the described elements or components and have no special meanings and are not used to represent a sequence. Unless otherwise specified, "(meth)acrylic acid", "(meth)acrylate" and similar terms used in this specification are intended to include both the groups within the brackets and the groups without them. For example, "(meth)acrylic acid" is intended to include acrylic acid and methacrylic acid, and "methyl (meth)acrylate" is intended to include methyl acrylate and methyl methacrylate. In the present specification and claims, the weight average molecular weight (Mw) is measured by gel permeation chromatography (GPC) and compared and converted with a standard product, and its unit is "g / mol". The present invention is more effective than the prior art in that, by controlling the gas chromatography properties of the photosensitive resin laminate, a high-thickness photosensitive resin laminate with good adhesion, storage and operability is provided. The following is a detailed description of the photosensitive resin laminate and its application. 1. Photosensitive resin laminate The photosensitive resin laminate of the present invention is a laminate composed of two or more photosensitive resin layers and contains a second component, and the second component can be contained in the photosensitive resin layer constituting the photosensitive resin laminate. In some embodiments of the present invention, the photosensitive resin laminate is composed of two to four photosensitive resin layers, and each of the photosensitive resin layers contains the second component. In some embodiments of the present invention, the photosensitive resin laminate does not substantially contain toluene, that is, the content of toluene is 0.5 wt % or less, such as 0.5 wt %, 0.45 wt %, 0.4 wt %, 0.35 wt %, 0.3 wt %, 0.25 wt %, 0.2 wt %, 0.15 wt %, 0.1 wt %, 0.05 wt %, or 0.01 wt %, based on the total weight of the photosensitive resin laminate. In some embodiments of the present invention, the photosensitive resin laminate does not contain toluene. The photosensitive resin laminate of the present invention can be used as a positive photoresist film or a negative photoresist film. In some embodiments of the present invention, the photosensitive resin laminate is used as a negative photoresist film, that is, after the photoresist film is exposed, the part not exposed to light will be dissolved during development, and the pattern of the exposed part will remain after development. The total thickness of the photosensitive resin laminate of the present invention is 100 μm to 600 μm. For example, the total thickness of the photosensitive resin laminate can be 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm, 310 μm, 320 μm, 330 μm, 340 μm, 350 μm, 360 μm, 370 μm, 380 μm, 390 μm, 400 μm, 410 μm, 420 μm, 430 μm, 440 μm, 450 μm, 460 μm, 470 μm, 480 μm, 490 μm, 500 μm, 510 μm, 520 μm, 530 μm, 540 μm, 550 μm, 560 μm, 570 μm, 580 μm, 590 μm, 600 μm, 610 μm, 620 μm, 630 μm, 640 μm, 650 μm, 660 μm, 670 μm, 680 μm, 690 μm, 700 μm, 710 μm, 720 μm, 730 μm, 740 μm, 750 μm, 760 μm, 360 micrometers, 370 micrometers, 380 micrometers, 390 micrometers, 400 micrometers, 410 micrometers, 420 micrometers, 430 micrometers, 440 micrometers, 450 micrometers, 460 micrometers, 470 micrometers, 480 micrometers, 490 micrometers, 500 micrometers, 510 micrometers, 520 micrometers, 530 micrometers, 540 micrometers, 550 micrometers, 560 micrometers, 570 micrometers, 580 micrometers, 590 micrometers, or 600 micrometers, or a range between any two of the above values. The higher the thickness of the photosensitive resin laminate, the higher the plating thickness of the metal conductive layer when used as a photoresist, so it is particularly suitable for 2.5D and 3D integrated circuit packaging, and can be used as a conductive layer before electroplating patterning application. 1.1. Gas chromatography properties of photosensitive resin laminates The photosensitive resin layered product of the present invention has specific gas chromatography properties. Specifically, when the photosensitive resin layered product of the present invention is characterized by gas chromatography with toluene added as an internal standard substance, it has an elution peak of the second component at 0.55 minutes to 1.30 minutes, an elution peak of toluene at 1.32 minutes to 1.65 minutes, and satisfies the following relationship: The units of the amount of toluene added and the mass of the photosensitive resin laminate are grams (g). In the above relationship, "0.1%-7.0%" means that the value calculated by the formula on the left side of the equal sign can be any value in the range of 0.1% to 7.0%. For example, in the above relationship, the value calculated by the formula on the left side of the equal sign can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7.0%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8.1%, 8. 5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.0%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, or 7.0%, or any value within the range consisting of any two of the above values. The gas chromatography analysis is performed by dissolving the photosensitive resin laminate in propylene glycol monomethyl ether and adding toluene as an internal standard substance to form a solution, and is performed under the following conditions: the column is a stainless steel column with a length of 3 meters, an outer diameter of 1 / 8 inches, and a wall thickness of 0.02 inches; the filler is a porous polymer stationary phase filler (Porous Polymer stationary phases); the carrier gas is nitrogen at a flow rate of 20 ml / min (mL / min), and the pressure at the helium source end is 5 kgf / cm2 (kgf / cm 2 ); the temperature rise condition is a step-by-step method, which is to maintain at 80°C for 0.1 minute, then increase from 80°C to 96°C at a heating rate of 4°C / min, then increase from 96°C to 135°C at a heating rate of 10°C / min, and maintain at 135°C for 2 minutes; the injection port temperature is 180°C; the solution injection volume is 3 microliters (μL); and the detector is a thermal conductivity detector at 200°C. In the aforementioned test conditions, the porous polymer stationary phase filler can be a CRS BX-10 column (purchased from Hengyi Company). The mass of the photosensitive resin laminate used in the gas chromatography analysis may be 11 g to 19.5 g, and the amount of toluene added in the gas chromatography analysis may be 0.45 g to 0.55 g. For example, the mass of the photosensitive resin laminate can be 11 g, 11.5 g, 12 g, 12.5 g, 13 g, 13.5 g, 14 g, 14.5 g, 15 g, 15.5 g, 16 g, 16.5 g, 17 g, 17.5 g, 18 g, 18.5 g, or 19 g, or within a range formed by any two of the above values; and the amount of toluene added can be 0.45 g, 0.46 g, 0.47 g, 0.48 g, 0.49 g, 0.50 g, 0.51 g, 0.52 g, 0.53 g, 0.54 g, or 0.55 g, or within a range formed by any two of the above values. In the gas chromatography analysis, it is preferred that the mass ratio of the photosensitive resin laminate used to the amount of toluene added is 25 to 35 times to obtain a better signal / noise ratio. In some embodiments of the present invention, the mass of the photosensitive resin layer used in the gas chromatography analysis is 15 grams, and the amount of toluene added is 0.50 grams to 0.53 grams. The mass of the propylene glycol monomethyl ether solvent used in the gas chromatography analysis can be 55 grams to 65 grams, for example, 55 grams, 56 grams, 57 grams, 58 grams, 59 grams, 60 grams, 61 grams, 62 grams, 63 grams, 64 grams, or 65 grams, or within the range formed by any two of the above values. In the gas chromatography, the elution time of propylene glycol monomethyl ether is later than the elution time of toluene. In some embodiments of the present invention, the time corresponding to the elution peak of propylene glycol monomethyl ether is equal to or later than 1.9 minutes. In some embodiments of the present invention, the time corresponding to the elution peak of propylene glycol monomethyl ether is 1.9 minutes to 6.9 minutes. 1.2. Photosensitive resin layer The photosensitive resin laminate of the present invention may be composed of two or more photosensitive resin layers, for example, two, three or four photosensitive resin layers, but the present invention is not limited thereto. The photosensitive resin layers may each independently have a thickness of 50 μm to 300 μm, for example, the thickness of the photosensitive resin layers may each independently be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, or 300 μm, or a range between any two of the above values. In some embodiments of the present invention, each of the photosensitive resin layers is independently a dry film, i.e., a photosensitive resin film with a low solvent content. The low solvent content refers to a solvent content of 0.1 wt % to 8 wt %, specifically 0.1 to 7 wt %, based on the total weight of the photosensitive resin film. Compared with a wet film in the form of ink or liquid, a dry film is less likely to flow or deform due to its low solvent content, and can be attached to a substrate without additional processes such as coating and drying, so it has the advantages of easy control and good operability. On the premise that the photosensitive resin laminate satisfies the aforementioned gas chromatography properties, the composition of the two or more photosensitive resin layers constituting the photosensitive resin laminate can be adjusted as needed, and the composition of each photosensitive resin layer can be the same as or different from each other. In some embodiments of the present invention, each photosensitive resin layer independently comprises: (A) an alkali-soluble polymer, (B) a component containing an ethylenically unsaturated compound, (C) a photopolymerization initiator, a second component, and optional additives. 1.2.1. (A) Alkali-soluble polymers Examples of alkali-soluble polymers include, but are not limited to, polymers having carboxyl groups, such as acrylic polymers having carboxyl groups, vinyl aromatic polymers having carboxyl groups, norbornene polymers having carboxyl groups, epoxy polymers having carboxyl groups, amide polymers having carboxyl groups, amide-epoxy polymers having carboxyl groups, alkyd polymers having carboxyl groups, and phenolic polymers having carboxyl groups. The aforementioned alkali-soluble polymers may be used alone or in combination. In some embodiments of the present invention, the alkali-soluble polymer is an acrylic polymer having a carboxyl group. The alkali-soluble polymer can be obtained, for example, by polymerizing one or more polymerizable monomers having a carboxyl group, or by copolymerizing one or more polymerizable monomers having a carboxyl group with other polymerizable monomers not having a carboxyl group, and thus may contain repeating units derived from a polymerizable monomer having a carboxyl group, or contain repeating units derived from a polymerizable monomer having a carboxyl group and repeating units of other polymerizable monomers. In some embodiments of the present invention, the alkali-soluble polymer has repeating units derived from at least one first polymerizable monomer and repeating units derived from at least one second polymerizable monomer, wherein the first polymerizable monomer has a carboxyl group, and examples thereof include but are not limited to (meth)acrylic acid, α-bromo(meth)acrylic acid, α-chloro(meth)acrylic acid, β-benzoimido(meth)acrylic acid, β-styryl(meth)acrylic acid, propiolic acid, fumaric acid, cinnamic acid, crotonic acid, itaconic acid, and maleic acid. The second polymerizable monomer does not have a carboxyl group, and examples thereof include, but are not limited to, (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, isooctyl (meth)acrylate (2-ethylhexyl (meth)acrylate), tertiary butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, 1-methyl-cyclopentyl (meth)acrylate, 1-methyl-cyclohexyl (meth)acrylate, 2-methyl-adamantyl (meth)acrylate, 2-ethyl (meth)acrylate, -adamantyl ester, 2-(meth)acrylate-2-butyl-adamantyl ester, (meth)acrylate tetrahydrofuran methyl ester, (meth)acrylate dimethylaminoethyl ester, (meth)acrylate diethylaminoethyl ester, (meth)acrylate glycidyl ester, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate; (meth)acrylonitrile; vinyl ester compounds, such as vinyl acetate and vinyl n-butyl ester; vinyl aromatic compounds, such as styrene, vinyl naphthalene, 3-acetoxystyrene, 4-acetoxystyrene, vinyl toluene, α-methylstyrene; norbornene; acrylamide; maleate compounds, such as monomethyl maleate, monoethyl maleate, monoisopropyl maleate; and derivatives of the aforementioned polymerizable monomers. The first monomer and the second monomer can be used independently or in combination. In a preferred embodiment of the present invention, the alkali-soluble polymer is obtained by copolymerizing (meth)acrylic acid with one or more (meth)acrylate compounds, and thus comprises repeating units derived from (meth)acrylic acid and repeating units derived from (meth)acrylate compounds. The weight ratio of (meth)acrylic acid to (meth)acrylate compounds may be 1:20 to 1:1, more specifically 1:6 to 1:4. For example, the weight ratio of (meth)acrylic acid to (meth)acrylate compounds may be 1:20, 1:19, 1:18, 1:17, 1:16, 1:15, 1:14, 1:13, 1:12, 1:11, 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, or 1:1, or a range consisting of any two of the above values. The weight average molecular weight (Mw) of the alkali-soluble polymer may be 10,000 to 180,000, preferably 40,000 to 80,000, for example 10,000, 15,000, 20,000, 25,000, 30,000, 35,000, 40,000, 45,000, 50,000, 55,000, 60,000, 65,000, 70,000, 75,000, 80,000, 85,000, 90,000, 91,000, 92,000, 93,000, 94,000, 95,000, 96,000, 97,000, 98,000, 99,000, 100,000, 101,000, 102,000 170,000, 175,000, or 180,000, or a range consisting of any two of the foregoing values. The content of the alkali-soluble polymer can be independently 20 wt % to 85 wt %, more specifically 40 wt % to 80 wt %, and even more specifically 50 wt % to 75 wt %, based on the weight of the photosensitive resin layer in which the alkali-soluble polymer is located. For example, the content of the alkali-soluble polymer can be 20 weight%, 22.5 weight%, 25 weight%, 27.5 weight%, 30 weight%, 32.5 weight%, 35 weight%, 37.5 weight%, 40 weight%, 42.5 weight%, 45 weight%, 47.5 weight%, 50 weight%, 52.5 weight%, 55 weight%, 57.5 weight%, 60 weight%, 62.5 weight%, 65 weight%, 67.5 weight%, 70 weight%, 72.5 weight%, 75 weight%, 77.5 weight%, 80 weight%, 82.5 weight%, or 85 weight%, or a range between any two of the above values. 1.2.2. (B) Components containing ethylenically unsaturated compounds The ethylenically unsaturated compound refers to a compound having at least one reactive ethylenic functional group, preferably a bifunctional compound having two reactive ethylenic functional groups. In some embodiments of the present invention, the ethylenically unsaturated compound comprises a monofunctional or multifunctional acrylate compound, and the monofunctional or multifunctional acrylate compound is preferably a difunctional acrylate compound, examples of which include but are not limited to ethoxylated bisphenol A dimethacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, ethoxylated bisphenol A diacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, polypropylene glycol diacrylate, tris((meth)acryloyloxyisocyanate)hexamethylene isocyanate, ethoxylated urate di(meth)acrylate, propoxylated urate di(meth)acrylate, ethoxylated / propoxylated urate di(meth)acrylate, ethoxylated tris(methacryloyloxyisocyanate)hexamethylene isocyanate, acrylated tris(methacryloyloxyisocyanate)hexamethylene isocyanate, and ethoxylated / propoxylated tris(methacryloyloxyisocyanate)hexamethylene isocyanate. In addition, in each photosensitive resin layer, the content of the bifunctional acrylate compound is preferably 60 weight % or more, based on the weight of the component containing the ethylenically unsaturated compound in the photosensitive resin layer, for example, 60 weight %, 62.5 weight %, 65 weight %, 67.5 weight %, 70 weight %, 72.5 weight %, 75 weight %, 77.5 weight %, 80 weight %, 82.5 weight %, 85 weight %, 87.5 weight %, 90 weight %, 92.5 weight %, 95 weight %, 97.5 weight %, or 100 weight %, or in a range consisting of any two of the above values. In some embodiments of the present invention, the component containing an ethylenically unsaturated compound comprises at least one of ethoxylated bisphenol A dimethacrylate and trimethylolpropane triacrylate. The content of the component containing the ethylenically unsaturated compound can be 5 to 70 weight % based on the weight of the photosensitive resin layer in which it is located, more specifically 15 to 50 weight % and even more specifically 20 to 45 weight %. For example, the content of the component containing ethylenically unsaturated compounds can be 5 weight%, 7.5 weight%, 10 weight%, 12.5 weight%, 15 weight%, 17.5 weight%, 20 weight%, 22.5 weight%, 25 weight%, 27.5 weight%, 30 weight%, 32.5 weight%, 35 weight%, 37.5 weight%, 40 weight%, 42.5 weight%, 45 weight%, 47.5 weight%, 50 weight%, 52.5 weight%, 55 weight%, 57.5 weight%, 60 weight%, 62.5 weight%, 65 weight%, 67.5 weight%, or 70 weight%, or a range between any two of the above values. 1.2.3. (C) Photopolymerization initiator Photopolymerization initiator refers to a substance that can initiate polymerization reaction under the action of light. The types of photopolymerization initiators are not particularly limited, and examples thereof include but are not limited to imidazole compounds, ketone compounds, quinone compounds, benzoin or benzoin ether compounds, polyhalogen compounds, triazine compounds, organic peroxides, onium salt compounds, and other photopolymerization initiators commonly used in the art. The aforementioned photopolymerization initiators can be used alone or in combination. Examples of the aforementioned imidazole compounds include, but are not limited to, 2,4,6-triaryl imidazole dimers, such as 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(m-methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, and 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer. Examples of the aforementioned ketone compounds include, but are not limited to, benzophenone, 4,4-bis(dimethylamino)benzophenone, 4-methoxy-4′-dimethylaminobenzophenone, 4,4′-dimethoxybenzophenone, 4-dimethylaminobenzophenone, 4-dimethylaminoacetophenone, xanthone, thioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, acridone, α-hydroxyacetophenone, α-aminoacetophenone, α-hydroxycycloalkylphenyl ketone, and dialkoxyacetophenone. Examples of the aforementioned quinone compounds include, but are not limited to, camphorquinone, benzylanthraquinone, 2-tert-butylanthraquinone, and 2-methylanthraquinone. Examples of the aforementioned benzoin or benzoin ether compounds include, but are not limited to, benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, and benzoin phenyl ether. Examples of the aforementioned polyhalogen compounds include, but are not limited to, carbon tetrabromide, phenyltribromomethyl sulfone, and phenyltrichloromethyl ketone. Examples of the aforementioned triazine compounds include, but are not limited to, 2,4,6-tris(trichloromethyl)-s-triazine, 2-methoxy-4,6-bis(trichloromethyl)-s-triazine, 2-amino-4,6-bis(trichloromethyl)-s-triazine, and 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine. Examples of the aforementioned organic peroxides include, but are not limited to, methyl ethyl ketone peroxide, cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, benzoyl peroxide, di-tertiary butyl peroxyisophthalate, 2,5-dimethyl-2,5-di(benzylperoxy)hexane, tertiary butyl peroxybenzoate, a,a'-bis(tertiary butylperoxyisopropyl)benzene, diisopropylbenzene peroxide, and 3,3',4,4'-tetrakis-(tertiary butylperoxycarbonyl)benzophenone. Examples of the aforementioned onium salt compounds include, but are not limited to, diaryl iodonium salts and triaryl sulfonium salts obtained by using a combination of biphenyl iodonium, 4,4′-dichlorobiphenyl iodonium, 4,4′-dimethoxybiphenyl iodonium, 4,4′-di-tert-butylbiphenyl iodonium, 4-methyl-4′-isopropyl-biphenyl iodonium or 3,3′-dinitrobiphenyl iodonium and chloride, bromide, tetrafluoroborate, hexafluorophosphate, hexafluoroarsenate, hexafluoroantimonate, and tetrakis(pentafluorophenyl)borate or trifluoromethanesulfonic acid. Examples of other common photopolymerization initiators in the art include, but are not limited to, fluorene, bisacylphosphine oxide compounds, azinium compounds, organic boron compounds, phenylglyoxylic acid esters, and titanocene. In some embodiments of the present invention, the photopolymerization initiator is an imidazole compound or a ketone compound. The content of the photopolymerization initiator can be 0.1 wt % to 15 wt %, more specifically 0.5 wt % to 10 wt %, and even more specifically 1 wt % to 5 wt %, based on the weight of the photosensitive resin layer in which the photopolymerization initiator is located. For example, the content of the photopolymerization initiator can be 0.1 weight%, 0.5 weight%, 1 weight%, 1.5 weight%, 2 weight%, 2.5 weight%, 3 weight%, 3.5 weight%, 4 weight%, 4.5 weight%, 5 weight%, 5.5 weight%, 6 weight%, 6.5 weight%, 7 weight%, 7.5 weight%, 8 weight%, 8.5 weight%, 9 weight%, 9.5 weight%, 10 weight%, 10.5 weight%, 11 weight%, 11.5 weight%, 12 weight%, 12.5 weight%, 13 weight%, 13.5 weight%, 14 weight%, 14.5 weight%, or 15 weight%, based on the weight of the photosensitive resin layer in which it is located, or a range between any two of the above values. 1.2.4. Second component In the present invention, the second component refers to a component having an elution peak at 0.55 minutes to 1.30 minutes when characterized by gas chromatography with toluene added as an internal standard substance. The second component may be present in at least one photosensitive resin layer, preferably in each photosensitive resin layer constituting the photosensitive resin laminate. In some embodiments of the present invention, the second component of each photosensitive resin layer may independently include at least one of inert esters, ketones, ethers, and alcohols having a boiling point of 55° C. to 90° C., wherein the inert esters, ketones, and alcohols are miscible with other components of the photosensitive resin layer but do not react with these other components. For example, the second component may include at least one of methyl acetate, ethyl acetate, acetone, methyl ethyl ketone, methanol, ethanol, and isopropanol. 1.2.5. Additives as needed On the premise that the photosensitive resin laminate satisfies the aforementioned gas chromatography properties, the two or more photosensitive resin layers constituting the photosensitive resin laminate may further contain additives to specifically improve the properties of the photosensitive resin layers. Examples of the additives include, but are not limited to, solvents, light absorbers, dyes, pigments, free radical inhibitors, and surfactants. Each of the additives may be used alone or in any combination. 1.3. Preparation of photosensitive resin laminate The preparation method of the photosensitive resin laminate of the present invention is not particularly limited. A person skilled in the art of the present invention can prepare the photosensitive resin laminate based on the disclosure of the present specification, especially the specific examples of the embodiments. Taking the exemplified photosensitive resin laminate described above as an example, it can be prepared by the following method: (A) an alkali-soluble polymer, (B) an ethylenically unsaturated compound, (C) a photopolymerization initiator, a second component, and other optional additives are uniformly mixed and dissolved or dispersed in a solvent with a stirrer to form a photosensitive liquid, and then the obtained photosensitive liquid is coated into a film and dried to obtain a photosensitive resin layer; the above steps are repeated, and the formulation of the photosensitive liquid is changed as needed to further obtain other photosensitive resin layers; the obtained photosensitive resin layers are stacked on each other and pressed or bonded to obtain a photosensitive resin laminate. In the present invention, the coating method of the photosensitive liquid is not particularly limited, and any coating method known in the art to which the present invention belongs can be used, including but not limited to gravure coating, reverse roll coating, die coating, air knife coating, knife coating, rod coating, bar coating, curtain coating, knife coating, transfer roll coating, extrusion coating, dip coating, kiss coating, spray coating, calendar coating, and extrusion coating. In some embodiments of the present invention, the coating method of the photosensitive liquid is preferably knife coating, rod coating, bar coating, or die coating. In some embodiments of the present invention, in order to make the photosensitive resin layer have an appropriate degree of dryness, it can be baked at a temperature of 70°C to 200°C for 1 to 40 minutes after coating the photosensitive liquid, preferably at a temperature of 100°C to 180°C for 1 to 40 minutes. The detailed preparation method of the photosensitive resin laminate is illustrated in the following examples. 2. Application of photosensitive resin laminates The photosensitive resin laminate of the present invention can be used as a photoresist film and further used in various electronic fields. Generally speaking, before using the photoresist film, a protective film that can provide protection and support functions is coated on both surfaces of the photoresist film to facilitate the storage of the photoresist film and prevent the photoresist film from adhering to foreign matter or being damaged. The photosensitive resin laminate of the present invention can also be provided with a protective film on its surface, and the protective film is preferably a non-photosensitive resin film. Therefore, the present invention further provides a composite laminate, comprising: the photosensitive resin laminate as described above; and a non-photosensitive resin film located on at least one surface of the photosensitive resin laminate. In a preferred embodiment of the present invention, the non-photosensitive resin film is formed on both surfaces of the photosensitive resin film, and the materials of the non-photosensitive resin films formed on the two surfaces of the photosensitive resin film can be the same or different. There is no particular limitation on the type of non-photosensitive resin film, and various materials available in the technical field to which the present invention belongs may be used. For example, the non-photosensitive resin film that can be used in the present invention may be selected from the following groups: polyethylene terephthalate film (PET film), polyolefin film, and the aforementioned composite. Examples of the polyolefin film include, but are not limited to, polyethylene film (PE film) and polypropylene film (PP film), such as oriented polypropylene film, and the composite may be a composite of polyethylene terephthalate film and polyolefin film, or a composite of different polyolefin films. In a preferred embodiment of the present invention, the composite laminate comprises a PET film formed on one surface of the photosensitive resin laminate and a PE film formed on the other surface of the photosensitive resin laminate. The preparation method of the composite laminate of the present invention is not particularly limited, and existing methods in the field to which the present invention belongs can be used. Based on the disclosure of the present specification, a person skilled in the art can prepare the laminate. For example, a non-photosensitive resin film can be laminated on two surfaces of a photosensitive resin laminate to provide a laminate, and the laminate is pressurized to obtain a composite film. Alternatively, a photosensitive resin layer can be formed between two non-photosensitive resin films by coating or extrusion, and then the non-photosensitive resin film on the surface of the photosensitive resin layer to be in contact with another photosensitive resin layer is torn off, and then laminated and pressurized to obtain a composite film. The detailed preparation method of the composite laminate can be referred to the embodiments shown below, which will not be described in detail here. 3. Example 3.1. Measurement method [Number of layers of photosensitive resin laminate] After cutting the obtained composite laminate into 10 mm x 15 mm at any position in the transverse direction (TD) and the machine direction (MD), remove the PE film and the PET film from both sides of the photosensitive resin laminate. Place the obtained photosensitive resin laminate sample on the analysis table of a microscope (model: Olympus MX51) with a jig, and adjust the position so that the cut surface of the sample is perpendicular to the observation direction of the objective lens. Use a fluorescent filter (model: WGSFluorescence Filter), a 10× objective lens (model: MPlanFL N), and a 10× eyepiece to observe the cut surface. Obvious interlayer interfaces can be observed, indicating that it has a laminate structure. Add one to the number of interfaces observed, which is the number of layers of the photosensitive resin laminate. [Gas chromatography analysis of photosensitive resin layer] After removing the PE film and PET film from both sides of the photosensitive resin laminate in the prepared composite laminate, cut the photosensitive resin laminate into 15-gram samples at any position in the transverse direction (TD) and the machine direction (MD). The obtained photosensitive resin laminate sample is dissolved in 60 grams of propylene glycol monomethyl ether, and 0.50 grams to 0.53 grams of toluene is added as an internal standard substance to form a solution. Gas chromatography analysis is performed under the following conditions: a stainless steel column with a length of 3 meters, an outer diameter of 1 / 8 inches, and a wall thickness of 0.02 inches is used as a filler; a column model CRS BX-10 (purchased from Hengyi Company) is used; the carrier gas is set to nitrogen with a flow rate of 20 milliliters per minute (mL / min), and the pressure at the helium source end is 5 kilograms of force per square centimeter (kgf / cm 2); the temperature rise condition is a step-by-step method, which is to maintain at 80°C for 0.1 minute, then increase from 80°C to 96°C at a rate of 4°C / min, then increase from 96°C to 135°C at a rate of 10°C / min, and maintain at 135°C for 2 minutes; the injection port temperature is 180°C; the solution injection volume is 3 microliters; and the detector is a thermal conductivity detector at 200°C. Xunhua Qchrom V1.2 software was used for analysis, and the calculation was performed according to the following formula, and the calculated values were recorded as "Gas Chromatography Calculation Results". [Bubble Analysis of Photosensitive Resin Laminate] The obtained composite laminate is cut into 10 cm × 15 cm pieces at any position in the transverse direction (TD) and the machine direction (MD), and the PE film is removed. Then, the photosensitive resin laminate together with the PET film thereon is placed on the transparent glass in a manner that the surface of the photosensitive resin laminate faces the transparent glass, and is placed in a molding machine for lamination under the following conditions: lamination rate of 0.5 m / min, lamination pressure of 3.0 kg / cm2, and lamination temperature of 25°C. After that, the PET film is removed, and the photosensitive resin laminate together with the glass is placed on a black flat substrate and exposed to an exposure energy of 100 mJ / cm2. A 1% Na2CO3 aqueous solution at 30°C is used as a developer, and the photosensitive resin laminate together with the glass is immersed in the developer for 10 minutes. After the development is completed, the photosensitive resin laminate together with the glass is taken out, washed with pure water for 10 seconds, and then blown dry with air. Randomly select a 5 cm x 5 cm area in the center of the glass for observation, divide the area into 100 small areas of 5 mm x 5 mm, and observe the bubbles in sequence under a microscope with a 10× objective lens and a 10× eyepiece. Based on the long diameter of the bubble, record the number of bubbles whose long diameter is greater than the total thickness of the photosensitive resin laminate × 0.5. [Wrinkle test of photosensitive resin laminate] The prepared composite laminate was rolled into a slit roll of 30 meters in length and 300 mm in width, and placed at a temperature of 23°C to 27°C for 16 hours. After that, a 5-meter-long composite laminate was pulled out from the slit roll and the PE protective film was torn off. The surface of the photosensitive resin film was then observed with the naked eye, and the number of wrinkles of 10 mm or more in length and 1 mm or more in width existing in the photosensitive resin film at a length of 3 to 5 meters was recorded. If wrinkles of 10 mm or more in length and 1 mm or more in width were not observed, it means that the storage and handling properties of the photosensitive resin laminate were good. [Hundred-grid test of photosensitive resin laminate] The adhesion test of the photosensitive resin laminate is carried out according to ASTM D3359 in the following manner. A copper foil laminate with a thickness of 1.6 mm (purchased from Chang Chun Man-Made Resin Factory Co., Ltd., model CCP-308) is prepared, wherein the copper foil thickness is 35 μm. It is brushed with a #320 non-woven brush wheel and a #600 non-woven brush wheel, and the surface temperature of the copper foil of the copper foil laminate is adjusted to 50°C. The PE film on the surface of the prepared composite laminate is torn off, and then the photosensitive resin laminate together with the PET film thereon is stacked on the copper foil surface in a manner that the photosensitive resin laminate faces the copper foil surface of the copper foil laminate, and then the sample is laminated with a laminating machine, wherein the laminating temperature is 80°C, the laminating pressure is 3.0 kg / cm2, and the laminating speed is 2.0 m / min. Remove the PET film on the sample and cut the photosensitive resin laminate on the sample into 10×10 squares with a total of 100 squares at intervals of 1 mm to 1.2 mm using a blade. Attach the transparent tape (model: 3M Transparent Tape 600) produced by 3M to the surface of the photosensitive resin laminate at the cut, then pull up the tape at an angle of 45 degrees to the substrate, and calculate and record the percentage of the number of squares peeled off from the photosensitive resin laminate to the total number of squares. The lower the percentage of the number of squares peeled off from the photosensitive resin laminate to the total number of squares, the better the adhesion of the photosensitive resin laminate to the copper foil laminate. 3.2. Preparation method 3.2.1. Synthesis of alkali-soluble polymers Acrylic polymers having a carboxyl group were prepared according to the following Synthesis Examples 1 to 7 as alkali-soluble polymers. [Synthesis example 1] 15 g of methacrylic acid, 60 g of methyl methacrylate, 25 g of butyl acrylate and 1.8 g of azobisisoheptanitrile as copolymer monomers were mixed to prepare solution a1. Separately, 0.7 g of azobisisoheptanitrile was dissolved in 20 g of ethyl acetate to prepare solution b1. A flask equipped with a stirrer, a reflux cooler, a thermometer, and a dropper was prepared, 80 g of ethyl acetate was added to the flask, and the mixture was heated to 70°C. Solution a1 was then added dropwise to the flask at a fixed rate for a total of 3 hours, and the temperature of the solution in the flask was maintained at 70°C and stirred for 2 hours. Then, the temperature of the solution in the flask was continued to be maintained at 70°C, and solution b1 was added dropwise to the flask at a fixed rate for a total of 0.5 hours, and the temperature of the solution in the flask was maintained at 70°C and stirred for 5 hours. After that, the solution in the flask was heated to 90°C and stirred for 5 hours to allow the reaction to proceed sufficiently. After the reaction was completed, the product was cooled to room temperature to obtain an acrylic acid polymer A having a carboxyl group (hereinafter also referred to as "polymer A") having a weight average molecular weight of 55,000 and a solid content of 50% by weight. [Synthesis example 2] 15 g of methacrylic acid, 65 g of methyl methacrylate, 20 g of butyl acrylate and 0.8 g of azobisisoheptanitrile as copolymer monomers were mixed to prepare solution a2. Separately, 0.5 g of azobisisoheptanitrile was dissolved in 20 g of methyl acetate to prepare solution b2. A flask equipped with a stirrer, a reflux cooler, a thermometer, and a dropper was prepared, 102.2 g of methyl acetate was added to the flask, and the mixture was heated to 70°C. Solution a2 was then added dropwise to the flask at a fixed rate for a total of 3 hours, and the temperature of the solution in the flask was maintained at 70°C and stirred for 2 hours. Then, the temperature of the solution in the flask was continued to be maintained at 70°C, and solution b2 was added dropwise to the flask at a fixed rate for a total of 0.5 hours, and the temperature of the solution in the flask was maintained at 70°C and stirred for 5 hours. After that, the solution in the flask was heated to 90°C and stirred for 5 hours to allow the reaction to proceed sufficiently. After the reaction was completed, the product was cooled to room temperature to obtain an acrylic acid polymer B having a carboxyl group (hereinafter also referred to as "polymer B") having a weight average molecular weight of 65,000 and a solid content of 45% by weight. [Synthesis example 3] 20 g of methacrylic acid, 40 g of methyl methacrylate, 40 g of 2-ethylhexyl acrylate and 1.2 g of azobisisohexyl nitrile as copolymer monomers were mixed to prepare solution a3. In addition, 0.5 g of azobisisohexyl nitrile was dissolved in 20 g of acetone to prepare solution b3. A flask equipped with a stirrer, a reflux cooler, a thermometer, and a dropper was prepared, 80 g of acetone was added to the flask, and the mixture was heated to 70°C. Solution a3 was then added dropwise to the flask at a fixed rate for a total of 3 hours, and the temperature of the solution in the flask was maintained at 70°C and stirred for 2 hours. Then, the temperature of the solution in the flask was continued to be maintained at 70°C, and solution b3 was added dropwise to the flask at a fixed rate for a total of 0.5 hours, and the temperature of the solution in the flask was maintained at 70°C and stirred for 6 hours. After that, the solution in the flask was heated to 90°C and stirred for 4 hours to allow the reaction to proceed sufficiently. After the reaction was completed, the resultant was cooled to room temperature to obtain an acrylic acid polymer C having a carboxyl group (hereinafter also referred to as "polymer C") having a weight average molecular weight of 55,000 and a solid content of 50% by weight. [Synthesis Example 4] 20 g of methacrylic acid, 60 g of methyl methacrylate, and 20 g of butyl acrylate as copolymer monomers were mixed with 1 g of azobisisoheptanitrile to prepare solution a4. Separately, 0.5 g of azobisisoheptanitrile was dissolved in 20 g of methyl ethyl ketone to prepare solution b4. A flask equipped with a stirrer, a reflux cooler, a thermometer, and a dropper was prepared, 80 g of methyl ethyl ketone was added to the flask, and the mixture was heated to 70°C. Solution a4 was then added dropwise to the flask at a fixed rate for a total of 4 hours, and the temperature of the solution in the flask was maintained at 70°C and stirred for 2 hours. Then, the temperature of the solution in the flask was continued to be maintained at 70°C, and solution b4 was added dropwise to the flask at a fixed rate for a total of 0.5 hours, and the temperature of the solution in the flask was maintained at 70°C and stirred for 5 hours. After that, the solution in the flask was heated to 90°C and stirred for 5 hours to allow the reaction to proceed sufficiently. After the reaction was completed, the resultant was cooled to room temperature to obtain an acrylic acid polymer D having a carboxyl group (hereinafter also referred to as "polymer D") having a weight average molecular weight of 50,000 and a solid content of 50% by weight. [Synthesis example 5] 20 g of methacrylic acid, 60 g of methyl methacrylate, 20 g of butyl acrylate and 1 g of azobisisoheptanenitrile as copolymer monomers were mixed to prepare solution a5. In addition, 0.5 g of azobisisoheptanenitrile was dissolved in a mixture of 10 g of propylene glycol methyl ether (PGME) and 10 g of ethyl acetate to prepare solution b5. A flask equipped with a stirrer, a reflux cooler, a thermometer, and a dropper was prepared, a mixture of 40 g of propylene glycol methyl ether and 40 g of ethyl acetate was added to the flask, and heated to 70°C, and then solution a5 was dripped into the flask at a fixed rate for a total of 3 hours, and then the temperature of the solution in the flask was maintained at 70°C and stirred for 2 hours. Then, the temperature of the solution in the flask was continued to be maintained at 70°C, and solution b5 was dripped into the flask at a fixed rate for a total of 0.5 hours, and then the temperature of the solution in the flask was maintained at 70°C and stirred for 5 hours. After that, the solution in the flask was heated to 90°C and stirred for 5 hours to allow the reaction to proceed fully. After the reaction was completed, the product was cooled to room temperature to obtain an acrylic acid polymer E (hereinafter also referred to as "polymer E") having a carboxyl group, the weight average molecular weight of which was 50,000 and the solid content was 50% by weight. [Synthesis example 6] 15 g of acrylic acid, 65 g of methyl methacrylate, 20 g of hydroxyethyl methacrylate and 1 g of azobisisoheptanitrile as copolymer monomers were mixed to prepare solution a6. In addition, 0.5 g of azobisisoheptanitrile was dissolved in a mixture of 4 g of ethanol and 16 g of ethyl acetate to prepare solution b6. A flask equipped with a stirrer, a reflux cooler, a thermometer, and a dropper was prepared, a mixed solution of 16 g of ethanol and 64 g of ethyl acetate was added to the flask, and heated to 70°C, and then solution a6 was dripped into the flask at a fixed rate for a total of 3 hours, and then the temperature of the solution in the flask was maintained at 70°C and stirred for 2 hours. Then, the temperature of the solution in the flask was continued to be maintained at 70°C, and solution b6 was dripped into the flask at a fixed rate for a total of 0.5 hours, and then the temperature of the solution in the flask was maintained at 70°C and stirred for 5 hours. After that, the solution in the flask was heated to 90°C and stirred for 5 hours to allow the reaction to proceed fully. After the reaction was completed, the product was cooled to room temperature to obtain an acrylic acid polymer F having a carboxyl group (hereinafter also referred to as "polymer F"), whose weight average molecular weight was 50,000 and solid content was 50% by weight. [Synthesis Example 7] 20 g of methacrylic acid, 45 g of methyl methacrylate, 35 g of isooctyl acrylate and 1.9 g of azobisisoheptanitrile as copolymer monomers were mixed to prepare solution a7. In addition, 0.5 g of azobisisoheptanitrile was dissolved in a mixture of 2 g of methanol and 18 g of methyl acetate to prepare solution b7. A flask equipped with a stirrer, a reflux cooler, a thermometer, and a dropper was prepared, a mixed solution of 8 g of methanol and 72 g of methyl acetate was added to the flask, and heated to 70°C, and then solution a7 was dripped into the flask at a fixed rate for a total of 3 hours, and then the temperature of the solution in the flask was maintained at 70°C and stirred for 2 hours. Then, the temperature of the solution in the flask was continued to be maintained at 70°C, and solution b7 was dripped into the flask at a fixed rate for a total of 0.5 hours, and then the temperature of the solution in the flask was maintained at 70°C and stirred for 5 hours. Thereafter, the solution in the flask was heated to 90°C and stirred for 5 hours to allow the reaction to proceed sufficiently. After the reaction was completed, the product was cooled to room temperature to obtain an acrylic acid polymer G having a carboxyl group (hereinafter also referred to as "polymer G"), whose weight average molecular weight was 45,000 and solid content was 50% by weight. 3.2.2. Preparation of photosensitive solution In the preparation of the following photosensitive solution, the raw material information used is shown in Table 1 below. Table 1 The photopolymerization initiator, additives, and THF solvent were mixed according to the component ratio shown in Table 2 and stirred for 30 minutes to form a mixed solution. Then, the alkali-soluble polymer and ethylenically unsaturated compound prepared in the synthesis example were added to the mixed solution and stirred for 1 hour, thereby obtaining photosensitive solutions A to H. Table 2 3.2.3. Preparation of photosensitive resin laminate According to Table 3-1 to Table 3-3, photosensitive resin layers having the required thickness of Examples E1 to E12 and Comparative Examples CE1 to CE15 were prepared respectively. Specifically, the photosensitive solution obtained above was coated on the PET film with a Kodaira wire bar, and then the coated photosensitive solution was dried in an oven to form a photosensitive resin layer on the PET film. Then, a PE film was covered on the surface of the photosensitive resin layer that did not contact the PET film to obtain photosensitive resin layers 1, 2, 3 and 4 coated on both sides. The PE film of the photosensitive resin layer 1 and the PET film of the photosensitive resin layer 2 are removed respectively, and then the photosensitive resin layer 1 and the photosensitive resin layer 2 are pressed together in a photosensitive resin layer-to-photosensitive resin layer manner to obtain a photosensitive resin laminate including the photosensitive resin layer 1 and the photosensitive resin layer 2. The PE film of the photosensitive resin layer 1 and the PET film of the photosensitive resin layer 2 are removed respectively, and then the photosensitive resin layer 1 and the photosensitive resin layer 2 are laminated in a photosensitive resin layer-to-photosensitive resin layer manner. The PE film of the photosensitive resin layer 2 is removed, and the PET film of the photosensitive resin layer 3 is removed, and then the photosensitive resin layer 3 is laminated as a photosensitive resin layer to the side of the photosensitive resin layer 2 that is not laminated to the photosensitive resin layer 1, and pressed to obtain a photosensitive resin laminate including the photosensitive resin layer 1, the photosensitive resin layer 2, and the photosensitive resin layer 3. The PE film of the photosensitive resin layer 1 and the PET film of the photosensitive resin layer 2 are removed respectively, and then the photosensitive resin layer 1 and the photosensitive resin layer 2 are laminated in a manner of photosensitive resin layer to photosensitive resin layer. The PE film of the photosensitive resin layer 2 is removed, and the PET film of the photosensitive resin layer 3 is removed, and then the photosensitive resin layer 3 is laminated to the side of the photosensitive resin layer 2 that is not laminated to the photosensitive resin layer 1. The PE film of the photosensitive resin layer 3 is removed, and the PET film of the photosensitive resin layer 4 is removed, and then the photosensitive resin layer 4 is laminated to the side of the photosensitive resin layer 3 that is not laminated to the photosensitive resin layer 2, and pressed to obtain a photosensitive resin laminate including the photosensitive resin layer 1, the photosensitive resin layer 2, the photosensitive resin layer 3, and the photosensitive resin layer 4. Table 3-1 Table 3-2 Table 3-3
[0100] 3.3. Test of photosensitive resin laminate
[0101] The various properties of the photosensitive resin laminates or photosensitive resin layers of Examples E1 to E12 and Comparative Examples CE1 to CE15 were measured according to the measurement methods described above, including the number of layers of the photosensitive resin laminates, the calculation results of gas chromatography, bubbles, wrinkles, and adhesion properties, and the results are recorded in the following Tables 4-1 to 4-3. Table 4-1 Table 4-2 Table 4-3 As shown in Table 4-1 to Table 4-3, the photosensitive resin laminate of the present invention has no bubble defects and no wrinkles, indicating that the photosensitive resin laminate has good operability and storage properties. In addition, the photosensitive resin laminates of Examples E1 to E12 show a low shedding ratio (<5%) in the 100-grid test, indicating good adhesion to the copper foil laminate. In contrast, the calculated results of gas chromatography of the photosensitive resin laminates of Comparative Examples CE1 to CE10 and CE15 are higher than the specified range (greater than 7.0%), so there are bubble defects and wrinkles, which means that the photosensitive resin laminate has poor operability and storage. The calculated results of gas chromatography of the photosensitive resin laminates of Comparative Examples CE11 and CE13 are lower than the specified range (less than 0.1), so there are bubble defects and poor adhesion. In particular, although Comparative Example CE13 has a photosensitive resin laminate structure, it still cannot provide the effect of the invention because the calculated results of gas chromatography are lower than the specified range. Although Comparative Example CE15 has a photosensitive resin laminate structure and a total thickness of 600 microns, it still cannot provide the effect of the invention because the calculated results of gas chromatography are higher than the specified range. This shows the importance of satisfying the technical features of the present invention related to gas chromatography. On the other hand, Comparative Example CE14 shows that even if the technical features of the present invention related to gas chromatography are met, if the photosensitive resin film does not have a laminated structure, bubbles and wrinkles will still exist. This shows the importance of having both the photosensitive resin laminated structure and the technical features of the present invention related to gas chromatography. In addition, the comparison between Example E4 and Comparative Example CE4, the comparison between Example E2 and Comparative Example CE5, the comparison between Example E7 and Comparative Example CE6, and the comparison between Example E11 and Comparative Example CE9 show that even if the total thickness of the formed laminate is the same, the comparative examples that do not use more than two photosensitive resin layers may not satisfy the aforementioned relationship, and thus a large number of bubbles and wrinkles appear. This shows the importance of the technical feature of having a photosensitive resin laminate structure. The above embodiments are only used to illustrate the principle and efficacy of the present invention and to describe the technical features of the present invention, and are not intended to limit the scope of protection of the present invention. Any changes or arrangements that can be easily completed by a person familiar with the present technology without violating the technical principle of the present invention are within the scope of the present invention.
Claims
1. A photosensitive resin laminate, characterized in that: It is composed of two or more photosensitive resin layers and contains a second component, wherein: When the photosensitive resin laminate is characterized by gas chromatography with toluene added as an internal standard substance, the second component has an elution peak at 0.55 minutes to 1.30 minutes, and a toluene elution peak at 1.32 minutes to 1.65 minutes, and the following relationship is satisfied: The units of the toluene addition amount and the mass of the photosensitive resin laminate are grams; and The total thickness of the photosensitive resin laminate is 100 micrometers to 600 micrometers.
2. The photosensitive resin laminate according to claim 1, wherein The gas chromatography analysis is performed by dissolving the photosensitive resin laminate in propylene glycol monomethyl ether and adding toluene as an internal standard substance to form a solution, and is carried out under the following conditions: the column is a stainless steel column with a length of 3 meters, an outer diameter of 1 / 8 inches, and a wall thickness of 0.02 inches; the filler is a porous polymer stationary phase filler; the carrier gas is nitrogen with a flow rate of 20 ml / min, and the pressure at the helium source end is 5 kgf / cm2; the heating condition is a step-by-step method, which is to maintain at 80°C for 0.1 minute, then increase from 80°C to 96°C at a heating rate of 4°C / min, then increase from 96°C to 135°C at a heating rate of 10°C / min, and maintain at 135°C for 2 minutes; the injection port temperature is 180°C; the solution injection volume is 3 μL; and the detector is a 200°C thermal conductivity detector.
3. The photosensitive resin laminate according to claim 1, wherein Each of these photosensitive resin layers independently has a thickness of 50 μm to 300 μm.
4. The photosensitive resin laminate according to any one of claims 1 to 3, wherein: It is composed of two to four photosensitive resin layers.
5. The photosensitive resin laminate according to any one of claims 1 to 3, wherein: Each of these photosensitive resin layers is independently a dry film.
6. The photosensitive resin laminate according to any one of claims 1 to 3, wherein: These photosensitive resin layers each independently comprise: (A) an alkali-soluble polymer; (B) a component containing an ethylenically unsaturated compound; and (C) Photopolymerization initiator.
7. The photosensitive resin laminate according to claim 6, wherein The ethylenically unsaturated compound-containing component (B) includes a bifunctional acrylate compound.
8. The photosensitive resin laminate according to claim 7, wherein The content of the bifunctional acrylate compound is 60% by weight or more based on the weight of the component (B) containing the ethylenically unsaturated compound.
9. A composite laminate, characterized in that: It contains: The photosensitive resin laminate according to any one of claims 1 to 8; and The non-photosensitive resin film is located on at least one surface of the photosensitive resin laminate.
10. The composite laminate according to claim 9, wherein: The non-photosensitive resin film is selected from the following group: polyethylene terephthalate film, polyolefin film and the above composites.
Citation Information
Patent Citations
Tricyclodecane dimethanol composition and uses thereof
US10767004B1
Method for manufacturing microstructure, method for manufacturing liquid ejection head, microstructure and liquid ejection head
US20230144597A1
KR20220140309A